2010
DOI: 10.1186/1471-2377-10-87
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural symptoms in patients with Alzheimer's disease and their association with cognitive impairment

Abstract: BackgroundBehavioural and psychological symptoms of dementia (BPSD) are non-cognitive symptoms commonly associated to Alzheimer's disease (AD). The characterization of the clinical profile of AD patients might help to better understand disease evolution and to improve diagnosis and treatment. Thus, the aim of the present study is to describe the clinical profile of AD patients, and to correlate the presence of BPSD with the severity of the disease.MethodsA cross-sectional, observational and multicenter study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 54 publications
9
82
0
5
Order By: Relevance
“…A study performed with 1014 patients, showed that 90% of the patients studied had BPSD, and 44% also showed depressive symptoms. In addition to this, the group also presented a high prevalence of other symptoms such as illusions, hallucinations and delusions in those patients with high scores in the scales of psychiatric symptoms (Fernandez et al 2010). Furthermore, depression and apathy appear more frequently during AD, with hallucinations, delusions and aggressiveness also being common .…”
Section: Introductionmentioning
confidence: 96%
“…A study performed with 1014 patients, showed that 90% of the patients studied had BPSD, and 44% also showed depressive symptoms. In addition to this, the group also presented a high prevalence of other symptoms such as illusions, hallucinations and delusions in those patients with high scores in the scales of psychiatric symptoms (Fernandez et al 2010). Furthermore, depression and apathy appear more frequently during AD, with hallucinations, delusions and aggressiveness also being common .…”
Section: Introductionmentioning
confidence: 96%
“…ADRD is characterized by cognitive impairment, a key antecedent to agitation [10][11][12]. Studies have reported agitation as high as 67.5% to 90% in persons with dementia [11,13].…”
Section: Agitation In Persons With Dementiamentioning
confidence: 99%
“…Studies have reported agitation as high as 67.5% to 90% in persons with dementia [11,13]. This is attributed to a progressive decline in the stress threshold resulting in an increased susceptibility to anxiety, advancing to agitation and without intervention culminating in catastrophic behaviors [3].…”
Section: Agitation In Persons With Dementiamentioning
confidence: 99%
“…Genepop version 4.0 was used to test the goodness of fit to the Hardy-Weinberg equilibrium (HWE), by means of the Guo-Thompson exact test [41] for two groups studied, and the hypothesis of heterozygote excess. The G test was also used to evaluate the differences between demographic and clinical variables, allele and genotype frequencies.…”
Section: Methodsmentioning
confidence: 99%